Costs and consumption of analgesics, with special reference to opiates in Serbia and Montenegro from 2015 to 2019 - Mladenović, Katarina; Dragojević Simić, Viktorija; Mugoša, Snežana; Rančić, Nemanja (Vojnosanitetski pregled, 2023)
Background/Aim. Patients in developing countries do not always receive adequate pain-relieving treatment. Monitoring analgesics consumption is of great importance since this can help assess the quality of painful condition management. The aim of this paper was to present a five-year consumption and costs of drugs with analgesic effects in developing countries, exemplified by Serbia and Montenegro, and indicate the main reasons for their (in)adequate prescribing. Methods. The observational, retrospective, cross-sectional study was conducted in order to analyze the consumption of all analgesics, both opioid and non-opioid, in Serbia and Montenegro, as developing countries. The data concerning analgesic consumption and drug prices were obtained from annual editions of the publications of the Medicines and Medical Devices Agency of Serbia and Montenegro. The World Health Organization methodology with defined daily dose (DDD) as a unit of measure (defined by the number of DDD per 1000 inhabitants per day) was used in these publications. Results. Over the course of five years (from 2015 to 2019) in Serbia, the total allocations for analgesic therapy had a rising trend, from about 43.6 million to 63.3 million euros, while in Montenegro, expenditures showed annual variations with the highest value in 2018. Most of the money in both countries was invested in the M01A group of drugs, for which the highest consumption was also recorded. Significantly higher consumption of opioid analgesics in Montenegro compared with Serbia was observed in the same period, and it predominantly reflected the difference in fentanyl (N02AB03, transdermal patch) prescribing. In Montenegro, consumption of the M01AB group of drugs was prominently higher in comparison to the M01AE drugs group during the whole five-year period, like in Serbia, in which this was not the case just in 2018. Conclusion. Taking into account the importance of analgesics for everyday medical practice, more rational prescribing of these drugs is necessary both in Serbia and Montenegro in the future.